2015
DOI: 10.1155/2015/208732
|View full text |Cite
|
Sign up to set email alerts
|

P-Chloroaniline Poisoning Causing Methemoglobinemia: A Case Report and Review of the Literature

Abstract: Background. Methemoglobin (MetHb) most commonly results from exposure to an oxidizing chemical but may also arise from genetic, dietary, or even idiopathic etiologies. P-chloroaniline (PCA) was one of the first substances described in the context of acquired methemoglobinemia. Case Report. We report the case of a cyanotic chemistry worker who presented to our emergency department (ED) after working with PCA. His peripheral oxygen saturation (SpO2) measured by pulse oximetry was at 81% and remained on that leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[1516] Studies found that PCA, apart from being proven carcinogenic in animals, also led to methemoglobinemia in humans. [1718] This is regardless of toxicity from PCA powder or the spontaneous breakdown of CHX. The International Agency for Research on Cancer (IARC, 2006) classified PCA as group 2B carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…[1516] Studies found that PCA, apart from being proven carcinogenic in animals, also led to methemoglobinemia in humans. [1718] This is regardless of toxicity from PCA powder or the spontaneous breakdown of CHX. The International Agency for Research on Cancer (IARC, 2006) classified PCA as group 2B carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this in vitro study is to determine whether PCA was formed as a byproduct of the reactions between NaOCl and final rinse CHX and QMix solutions, as well as a result of EDTA/CHX combination. This can be important because PCA is considered to be cytotoxic on human cells (WORLD HEALTH ORGANISATION, 2006), carcinogenic (THOMAS et al, 2010) and can lead to neonates methemoglobinemia (MESSMER et al, 2015). TLC, 1 H NMR and IR methods were chosen for this study due to their great sensitivity in identifying components of a given reaction mixture, as well as determination of mixture purity.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, recently, the brown precipitate has been reported as toxic on both Caenorhabditis elegans and primary immortalized human gingival fibroblasts (Jeong et al, 2021). PCA, 4-chloroaniline or ClC6H4NH2 is known to be toxic (Boehncke et al, 2003), carcinogenic (Chhabra et al, 1991), and may lead to cyanosis related to methemoglobinemia (Kulkarni et al, 1969;Messmer et al, 2015;Ramsay & Harvey, 1959) in mammals, see Figure 2. According to the universal regulation, acute toxicity of PCA is corresponds to 'Category 3' if swallowed, inhaled or contacted.…”
Section: What Does Not Form After Accidental Sodium Hypochlorite Cont...mentioning
confidence: 99%